Investigation of matrix independent calibration of oxygen in glow discharge optical emission spectrometry. Issue 6 (6th May 2022) - Hoffmann, Volker; Gebel, Bernhard; Heller, René; Gemming, Thomas
Abstract : Emission intensity of oxygen at 777 nm in Cu-, Al-, Mg- and Fe-matrices. Abstract : The performance of glow discharge optical emission spectrometry for matrix independent oxygen determination was investigated using the spectral lines of atomic oxygen at 130 nm and 777 nm and standard conditions for dc discharge with a 4 mm anode (700 V, 20 mA). Using hot-pressed calibration samples of Cu-, Al- and Mg-powder mixed with their oxides, at 130 nm the dependence of the emission yield on these matrices was confirmed. However, at 777 nm oxygen has the same emission yield in these matrices. In order to compare the emission yield of oxygen with the emission yield in iron a thick 43 μm FeO-layer was prepared and characterized by Rutherford backscattering spectrometry, X-ray diffraction and glow discharge optical emission spectrometry. At 130 nm, the emission yield of oxygen in FeO is most similar to that in an Al-matrix. At 777 nm, the calibration revealed a higher emission yield of oxygen in FeO in comparison to the common emission yield of oxygen in Cu-, Al- and Mg-matrices.